Enhanced selective ammonia detection of spray deposited Cd-doped β-Ga2O3 thin films with low hysteresis effect. Issue 19 (1st October 2022) - Pandeeswari, R.; Jeyaprakash, B.G.; Veluswamy, Pandiyarasan; Balamurugan, D.
Abstract: The Ga2 O3 thin films at different concentrations (at %) of Cd dopant were deposited using spray pyrolysis technique. The X-ray diffraction patterns revealed Cd-doped β-Ga2 O3 thin film are in monoclinic crystal structure with (2 0 1) orientation. Atomic force micrographs depict the change in morphology upon Cd dopant. At ambient temperature (∼30 °C), the results of ammonia sensing measurements of 4 at % Cd-doped Ga2 O3 thin films point out the low-level detection (0.5 ppm) of ammonia with good sensing response (233 %), higher sensitivity (26 Ω/m), fast response-recovery time (3 s and 14 s), better selectivity, low hysteresis, and higher stability. Graphical abstract: Maiden report of spray deposited Cd-doped β-Ga2 O3 thin films shows selective detection and greater sensing response (S = 233%) towards ammonia vapour (0.5 ppm) by chemi-resistive method. Image 1